If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 1) + -3x = -9 Reorder the terms: 6(1 + x) + -3x = -9 (1 * 6 + x * 6) + -3x = -9 (6 + 6x) + -3x = -9 Combine like terms: 6x + -3x = 3x 6 + 3x = -9 Solving 6 + 3x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = -9 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = -9 + -6 3x = -9 + -6 Combine like terms: -9 + -6 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| -5a+2+6a=5-30 | | 5-x^2=3-x | | 2x-8/4=9 | | x^2+5x-43=7 | | -2(x-4)-12=16 | | -2(x+2)-8=10 | | 3a+6a=2a | | -5(5x+1)=45 | | 8-2(4y+12)=18 | | n-9= | | 3x*x-2=5x | | y=4x^2-9x-9 | | 3.5/.75x | | y=-3-3/5x | | y=-1/2x2-1 | | 1.07x+5=30 | | 1.7x+5=30 | | 7*6+7= | | 3.5x=.74 | | f(-6)=-3-4 | | b/13-3b/=8/13 | | W=4.2-2L/2 | | 3y=-4x+30 | | $10-3/5= | | 378t-9/7t^2 | | q=2.1 | | Y-5=0(X+3) | | X/7=6-(-8) | | 3x+2x+10=5(x+10) | | 10+15*4= | | 5w-w=8 | | 10.47=2(3.14)(6)(m/360) |